COMPETENCY SKILLS FOR JAKHAY SOLO - Poumanee, Chortip (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2022)
This article aims to transfer the knowledge of Competency Skills for Jakhay Solo from researching treatise and interviewing the expert who can provide the information about competency skill of Jakhay Solo. The research found that the essential element of Competency Skills for Jakhay Solo consisted of professional competence that the performer should have which are knowledge, skill, ability to perform the show successfully, and the positive attitude to the assignment. The competency of musical profession can be able to perform variously. The determination by qualified expert can help to specify the knowledge, skills and attitude for each competent performer. For example, musician must have core competency for musical instrument performance. Musical instrument performance is a core competency that Thai Musical Profession must have knowledge, ability, and good skill of performance. The Performance of string musical instrument which the author shall mention in this article is Jakhay which is Thai String Musical Instrument which is widely popular nowadays. Jakhay is string instrument which has three stretching string, plucking the string with finger to make sound. In the old day, the string instrument has 1 or 2 strings only. Recently Jakhay was developed to have many strings with fret in order to make difference of various sounds. The role of Jakhay instrument is not only for ensemble but also for solo. To perform Jakhay Solo, the performer must have accuracy of core melody; play correctly according to the composer’s original melody. The qualification of Jakhay Solo Performer must be well- practiced, able to study history, element, method, technique of Solo. The performer must precisely remember the melody and overlay rhythm, pay attention to the details of song and also repeat practicing regularly in order to keep proficiency and provide the audience a sense of exquisitority of Solo. The performer should be able to solve problem immediately while performing as well. From the above mention about the competency of Jakhay Solo, the performer must not only have high proficiency of music performance but also perform the song correctly in accordance with Thai Musical Principal in order to achieve the objectives of the composer.